Corneal confocal microscopy: ready for prime time. (4th March 2019) - Petropoulos, Ioannis N; Ponirakis, Georgios; Khan, Adnan; Gad, Hoda; Almuhannadi, Hamad; Brines, Michael; Cerami, Anthony; Malik, Rayaz A
Abstract : Corneal confocal microscopy is a non‐invasive ophthalmic imaging modality, which was initially used for the diagnosis and management of corneal diseases. However, over the last 20 years it has come to the forefront as a rapid, non‐invasive, reiterative, cost‐effective imaging biomarker for neurodegeneration. The human cornea is endowed with the densest network of sensory unmyelinated axons, anywhere in the body. A robust body of evidence shows that corneal confocal microscopy is a reliable and reproducible method to quantify corneal nerve morphology. Changes in corneal nerve morphology precede or relate to clinical manifestations of peripheral and central neurodegenerative conditions. Moreover, in clinical intervention trials, corneal nerve regeneration occurs early and predicts functional gains in trials of neuroprotection. In view of these findings, it is timely to summarise the knowledge in this area of research and to explain why the case for corneal confocal microscopy is sufficiently compelling to argue for its inclusion as a Food and Drug Administration endpoint in clinical trials of peripheral and central neurodegenerative conditions.